2015
DOI: 10.1016/s2215-0366(15)00086-3
|View full text |Cite
|
Sign up to set email alerts
|

Supporting recovery in patients with psychosis through care by community-based adult mental health teams (REFOCUS): a multisite, cluster, randomised, controlled trial

Abstract: (2015) Supporting recovery in patients with psychosis using adult mental health teams (REFOCUS): a multi-site cluster randomised controlled trial. The Lancet Psychiatry, 2 (6). pp. 503-514. ISSN 2215-0374 Access from the University of Nottingham repository: http://eprints.nottingham.ac.uk/34258/1/AFD%20Lancet%20Psychiatry%20REFOCUS %20Cost-effectiveness.pdf Copyright and reuse:The Nottingham ePrints service makes this work by researchers of the University of Nottingham available open access under the follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
108
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 108 publications
(118 citation statements)
references
References 33 publications
4
108
1
2
Order By: Relevance
“…Although staff training in recovery-oriented practice is a common model, a major trial of training in recovery-oriented practice observed limited impact on a measure of these recovery processes [37]. On the other hand, positive outcomes for measures of recovery have been found for group-format self-management interventions that incorporate material on recovery [1113].…”
Section: Introductionmentioning
confidence: 99%
“…Although staff training in recovery-oriented practice is a common model, a major trial of training in recovery-oriented practice observed limited impact on a measure of these recovery processes [37]. On the other hand, positive outcomes for measures of recovery have been found for group-format self-management interventions that incorporate material on recovery [1113].…”
Section: Introductionmentioning
confidence: 99%
“…The original 8 studies from which the full sample was drawn consisted of: (1) a Nordic multisite study [7], which investigated predictors of subjective well-being in community patients with schizophrenia in the 5 Nordic countries; (2) an explanatory-model study [8] comparing patients’ explanatory models for schizophrenia across 4 ethnic groups in a London community sample; (3) the DIALOG trial [9], which tested the effectiveness of a structured patient-clinician communication intervention in community samples across 6 European countries; (4) the EDEN trial [10], which compared day hospital versus inpatient treatment in 5 European countries; (5) InvolvE [11], which followed patients who had been involuntarily admitted to 22 UK hospitals; (6) EPOS [12], which tested the advanced DIALOG+ intervention involving a patient-centred solution-focused approach in a London community sample; (7) REFOCUS [13], a 2-site cluster randomised controlled trial testing the effectiveness of a staff-based intervention on recovery for patients with psychosis in England; and (8) NESS [14], which was a randomized controlled trial to examine the effectiveness of body psychotherapy for schizophrenia in several UK sites.…”
Section: Methodsmentioning
confidence: 99%
“…The present study was conducted as part of a wider process evaluation nested within the REFOCUS RCT [21]. Within the RCT there were no group differences in recovery scores at the end of the intervention.…”
Section: 'If You've Lost Hope Then You've Lost Life (…) So It's Good mentioning
confidence: 99%
“…Service users described how being 'genuinely' caring and supportive, as well as honest and open in a constructive manner, were necessary qualities of staff. [21] …”
Section: Implications For Practicementioning
confidence: 99%
See 1 more Smart Citation